Experimental studies on micro powder hot embossing for high-aspect-ratio microstructures with ultra-high molecular weight polyethylene powders. (31st August 2020) - Gao, Jie; Peng, Linfa; Deng, Yujun; Yi, Peiyun; Lin, Zhongqin
Abstract: High-aspect-ratio microstructures have broad application prospects in many fields. Conventionally, lithography and etching processes are the primary methods for fabricating high-aspect-ratio microstructures on glass or silicon chips. However, as application scenarios have expanded, polymeric microstructures have received increasing attention, due to the low cost and wide ranges of special physical properties of polymers. Hot embossing is a high-efficiency method of processing large-area polymer films, but due to spring back, fabricating high-aspect-ratio microstructures remains a challenge. For this issue, micro powder hot embossing with the advantage of the good fluidity of the powder, is expected to achieve accurate microstructures with a high aspect ratio. In this paper, micro powder hot embossing was studied experimentally with the ultra-high molecular weight polyethylene (UHMWPE) powders which has excellent performances but poor formability. First, the processing window for preparing compact samples was investigated. Two indicators including filling depth and compactness were then proposed to characterize the forming quality of high-aspect-ratio microstructures. Afterwards, the effect of cavity size was also discussed and a ratio of cavity size to powder particle size was suggested to exceed 4 for high-aspect-ratio microstructures. Lastly, influences of process parameters (including temperature, pressure, and sintering duration) were further studied, which recommends a loading pressure greater than 10 MPa and a sintering temperature exceeding 140 °C for the micro powder micro embossing for UHMWPE. Microgrooves with an aspect ratio up to 8.0 were successfully prepared, demonstrating the feasibility of micro powder hot embossing in the fabrication of high-aspect-ratio microstructures with high precision and comprehensive properties.